A new approach to assess canoe performance through functional electromechanical dynamometry - Álvarez-Yates, T.; Cuba-Dorado, A.; Serrano-Gómez, V.; Vila-Suárez, H.; Nakamura, F. Y.; García-García, O. (International Journal of Sports Medicine, 2026)
The aim of this study was to evaluate the predictive capacity of functional electromechanical dynamometry for sprint canoe performance. Twenty-one world-class sprint canoeists underwent two functional electromechanical dynamometry assessments (isometric and incremental load) in the sprint canoe-specific kneeling position. Race performance was assessed via official C1 500-m race times. Significant negative correlations were observed between 500-m race times and both the mean force (r=-0.72; p=0.001) and the peak force (r=-0.71; p=0.001) measured through the isometric dynamometric test. In the incremental test, a strong negative correlation was found between the race time and the number of strokes (Nreps; r=-0.85; p=0.001), as well as the absolute peak force (r=-0.80; p=0.001). These relationships remained significant when force values were adjusted for body mass. The strongest predictive model (R2 a=0.73) included the number of strokes from the incremental load test (C1 500-m race time=170.30-3.29 Nreps). These findings support the use of functional electromechanical dynamometry as a valid and sport-specific tool for assessing neuromuscular performance in elite sprint canoeists.